2011
DOI: 10.1007/s00228-011-1099-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the consumption rates and regulatory barriers to the accessibility of strong opioid analgesics in Israel and St. Petersburg

Abstract: The results suggest that strong opioid analgesics consumption rates in St. Petersburg yield those in Israel, and that the between-countries differences in opioid formularies availability and legal and regulatory barriers to opioids accessibility are responsible for the consumption discrepancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A longitudinal study in the United States found that baseline reporting of drinking to cope was associated with subsequent drinking problems (Holahan et al, 2001), and among persons being treated for substance use disorders, persistent pain has been associated with a lower likelihood of being abstinent of alcohol or drugs in the future (Caldeiro et al, 2008; Larson et al, 2007). Because opioids are not typically prescribed for chronic pain management in Russia (Ponizovsky et al, 2012), it is conceivable that persons with pain might be more likely to turn to a legal, culturally sanctioned substance like alcohol to treat pain and pain-related stress. Effective pain management services may prove useful to reduce unforeseen consequences like unhealthy alcohol use among HIV-infected persons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study in the United States found that baseline reporting of drinking to cope was associated with subsequent drinking problems (Holahan et al, 2001), and among persons being treated for substance use disorders, persistent pain has been associated with a lower likelihood of being abstinent of alcohol or drugs in the future (Caldeiro et al, 2008; Larson et al, 2007). Because opioids are not typically prescribed for chronic pain management in Russia (Ponizovsky et al, 2012), it is conceivable that persons with pain might be more likely to turn to a legal, culturally sanctioned substance like alcohol to treat pain and pain-related stress. Effective pain management services may prove useful to reduce unforeseen consequences like unhealthy alcohol use among HIV-infected persons.…”
Section: Discussionmentioning
confidence: 99%
“…Important differences in the management of pain exist between the United States/Western Europe and Russia. Restrictive policies toward the medical use of opioids in Russia results in opioids being less frequently prescribed for pain (Ponizovsky et al, 2012). Given that opioids are not generally prescribed for treatment of pain, it is possible that HIV-infected patients in Russia with pain might turn to other substances to relieve their pain.…”
Section: Introductionmentioning
confidence: 99%
“…The INCB is actively monitoring opioid consumption worldwide to improve and control national policies of opioid use . The aim is to provide adequate medical access to the formularies, both organizationally and legally, for those needing it while establishing effective ways to control opioid accessibility to prevent illegal trafficking …”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent comprehensive survey of medical opioid availability and accessibility in Middle East countries (Egypt, Yemen, Israel, Qatar, Saudi Arabia, Algeria, Iran, Morocco, Syria, Afghanistan, Iraq, Lebanon, Libya, the OPT, and Tunisia) found that with the exception of Israel, opioid availability was low because of deficiencies in opioid formularies and restricted access resulting from widespread over‐regulation across the region . A similar situation has been observed in the Russian Federation as well, where because of pervasive over‐regulation, accessibility to opioid analgesics is low (compared to Israel) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation